2007
DOI: 10.1007/s00426-007-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple response codes play specific roles in response selection and inhibition under task switching

Abstract: Several task-switch studies show that response category repetition is favorable on task repetition trials, but disadvantageous on task switch trials. In the present study we investigated how this interaction depends on the type and number of involved response categories. In a dual-task number-categorization experiment, subjects had to respond to tasks T 1 and T 2 with one of the two Wngers of their left and right hand, respectively. For one group of participants, the use of spatial response categories, and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…a ‘change all’ signal), (ii) increased difficulty uncoupling recently established stimulus-response mappings, or (iii) the selective suppression of the last-executed (and possibly still active) response (Rogers & Monsell, 1995). Current behavioral evidence more strongly supports the latter, selective suppression, hypothesis (Cooper & Mari-Beffa, 2008; Hübner & Druey, 2006, 2008). We speculate that this difficulty in repeating the same response when a switch occurs might be a ‘built in’ basal ganglia design, consistent with the computational requirement for a clean switch to prevent dithering (Redgrave, Prescott, & Gurney, 1999).…”
Section: Discussionsupporting
confidence: 52%
“…a ‘change all’ signal), (ii) increased difficulty uncoupling recently established stimulus-response mappings, or (iii) the selective suppression of the last-executed (and possibly still active) response (Rogers & Monsell, 1995). Current behavioral evidence more strongly supports the latter, selective suppression, hypothesis (Cooper & Mari-Beffa, 2008; Hübner & Druey, 2006, 2008). We speculate that this difficulty in repeating the same response when a switch occurs might be a ‘built in’ basal ganglia design, consistent with the computational requirement for a clean switch to prevent dithering (Redgrave, Prescott, & Gurney, 1999).…”
Section: Discussionsupporting
confidence: 52%
“…It is likely that these two possible factors cause the non-significant difference in RT between the rule inhibition and non-inhibition conditions. The RTs for the response inhibition condition was significantly longer than the non-inhibition condition, reflecting response inhibition and response change 66 , 67 , 77 .…”
Section: Discussionmentioning
confidence: 90%
“…If the current trial in a flanker task had the identical stimulus and the same response as the preceding trial, there would be a response repetition benefit 66 70 . In the classical choice RT tasks, identical stimulus-reaction (S-R) trials are usually associated with particularly fast responses, which is suggested to reflect remission of the same and the most recent response on detection of an identical stimulus reoccurrence 71 73 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, faster performance in the task repetition condition might, in part, be explained by these stimulus repetitions. Although stimulus repetitions are sometimes disallowed in the procedure or trimmed after the fact [ 26 28 ], this is not always the case.…”
Section: Introductionmentioning
confidence: 99%